2019
DOI: 10.1155/2019/4310319
|View full text |Cite
|
Sign up to set email alerts
|

Psoralea corylifoliaL. Seed Extract Attenuates Methylglyoxal-Induced Insulin Resistance by Inhibition of Advanced Glycation End Product Formation

Abstract: Accumulation of advanced glycation end products (AGEs) in the body has been implicated in the pathogenesis of metabolic conditions, such as diabetes mellitus. Methylglyoxal (MGO), a major precursor of AGEs, has been reported to induce insulin resistance in both in vitro and in vivo studies. Psoralea corylifolia seeds (PCS) have been used as a traditional medicine for several diseases, but their potential application in treating insulin resistance has not yet been evaluated. This study is aimed at investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Insulin resistance was observed after MG i.v. injection (50 mg/Kg) or administration in the drinking water (1%) to Sprague-Dawley rats [54][55][56]. Moreover, diets enriched with AGEs and MG-BSA were also shown to produce similar results, namely glucose intolerance and lower insulin receptor activation in muscle, liver, and adipose tissue.…”
Section: Development Of Animal Modelsmentioning
confidence: 88%
“…Insulin resistance was observed after MG i.v. injection (50 mg/Kg) or administration in the drinking water (1%) to Sprague-Dawley rats [54][55][56]. Moreover, diets enriched with AGEs and MG-BSA were also shown to produce similar results, namely glucose intolerance and lower insulin receptor activation in muscle, liver, and adipose tissue.…”
Section: Development Of Animal Modelsmentioning
confidence: 88%
“…Our result was also consistent with and similar to previous reports. Seo E et al found that P. corylifolia L. could improve renal function by repressing insulin resistance, renal fibrosis, and apoptosis in diabetic mice (Seo, Kang, Oh, & Jun, 2017;Seo et al, 2014;Truong et al, 2019). P. corylifolia L. oral extract taken at a dose of 500 mg/kg showed hypoglycaemic effects on diabetic mice, but no hypoglycaemic effects were observed from P. corylifolia L. extract at a dose of 200 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in in vitro studies, ISO has been proven to block the activation of several inflammatory molecules and reduce intercellular cell adhesion molecule-1 (ICAM-1) and inducible nitric oxide synthase expression in vitro (Lee, Kim, Baik, Ryu, & Lee, 2015;Shin, Shon, & Youn, 2013). Specifically, certain recent studies found that P. corylifolia L. seed extract not only improves insulin resistance but also ameliorates diabetes by the inhibition of oxidative stress (Seo et al, 2014;Truong, Seo, & Jun, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its extensive clinical effects [10, 11], P. corylifolia has earned a high reputationthroughout the history of traditional Chinese medicine. In recent years, it has also been found to be effective in treating diabetes, psoriasis and other diseases [12][13][14][15][16].Compared with synthetic compounds,, natural active components in plants have been pre-screened by the natural environment, which ensures their stability, bioavailability, and biological activity. Understanding their biosynthetic pathways is important for the effective synthesis of these natural products in vitro [17].…”
mentioning
confidence: 99%
“…Owing to its extensive clinical effects [10, 11], P. corylifolia has earned a high reputationthroughout the history of traditional Chinese medicine. In recent years, it has also been found to be effective in treating diabetes, psoriasis and other diseases [12][13][14][15][16].…”
mentioning
confidence: 99%